Knowledge, Attitudes and Practices to Sunscreen Use among Dermatology Patients at University Hospital Amman, Jordan: A Cross-Sectional Study - Murshdi, Rand; Ammouri, Rama; Barghouthi , Yazan; AlSamhouri, Jehad; Ammouri , Rania; AlQaysi, Hasan; Murshdi , Raghad; Abdallat , Mahmoud (Jordan Medical Journal, 2024)
Background and Aims: Skin cancer is a significant public health concern globally. Jordan’s location and high exposure to UV radiation have led to an increase in the incidence rate of skin cancer. This study aimed to investigate the knowledge, attitudes, and practices of patients to sunscreen use in one of the major hospitals in Jordan, and identify demographic factors associated with regular sunscreen use. Methodology: An observational cross-sectional study was conducted at the dermatology clinic of Jordan University Hospital, Amman, Jordan, from February 2, 2023 to March 6, 2023. The study included 397 participants recruited from the clinic’s waiting area. A validated survey questionnaire was used to collect data on demographics, previous skin cancer history, sunscreen allergies, knowledge, attitudes, and practices related to sunscreen use. The data were analyzed using SPSS v. 26. Statistical significance was established at a p-value of <0.05. Results: The majority of participants were female (67.0%) and aged 18–25 years (53.7%). Only 24.9% of participants reported using sunscreen regularly, while 34.0% reported never using it. Participants with higher education levels and income were more likely to use sunscreen regularly. The main sources of sunscreen recommendations were family and friends (48.1%), followed by dermatologists (32.7%). The most common reason for not using sunscreen was forgetfulness (40.1%). Conclusion: The study revealed that knowledge and practices related to sunscreen use among Jordanian dermatology patients are insufficient, and that there is a need for increased patient education regarding the importance of sunscreen use.